A new method of fabricating a blend scaffold using an indirect three-dimensional printing technique. (2nd November 2015) - Jung, Jin Woo; Lee, Hyungseok; Hong, Jung Min; Park, Jeong Hun; Shim, Jung Hee; Choi, Tae Hyun; Cho, Dong-Woo
Abstract: Due to its simplicity and effectiveness, the physical blending of polymers is considered to be a practical strategy for developing a versatile scaffold having desirable mechanical and biochemical properties. In the present work, an indirect three-dimensional (i3D) printing technique was proposed to fabricate a 3D free-form scaffold using a blend of immiscible materials, such as polycaprolactone (PCL) and gelatin. The i3D printing technique includes 3D printing of a mold and a sacrificial molding process. PCL/chloroform and gelatin/water were physically mixed to prepare the blend solution, which was subsequently injected into the cavity of a 3D printed mold. After solvent removal and gelatin cross-linking, the mold was dissolved to obtain a PCL–gelatin (PG) scaffold, with a specific 3D structure. Scanning electron microscopy and Fourier transform infrared spectroscopy analysis indicated that PCL masses and gelatin fibers in the PG scaffold homogenously coexisted without chemical bonding. Compression tests confirmed that gelatin incorporation into the PCL enhanced its mechanical flexibility and softness, to the point of being suitable for soft-tissue engineering, as opposed to pure PCL. Human adipose-derived stem cells, cultured on a PG scaffold, exhibited enhanced in vitro chondrogenic differentiation and tissue formation, compared with those on a PCL scaffold. The i3D printing technique can be used to blend a variety of materials, facilitating 3D scaffold fabrication for specific tissue regeneration. Furthermore, this convenient and versatile technique may lead to wider application of 3D printing in tissue engineering.